Attitudes of small and medium-sized chemical companies towards information sharing within supply chains - Paták, Michal; Branská, Lenka; Pecinová, Zuzana; Janata, Daniel (TANGER, spol. s r.o., 2019)
Information sharing within a supply chain has a number of positive impacts on its performance. However, to achieve highly effective communication, it is necessary that there are trust-based business partnerships and willingness to share correct and for the partner important information in the supply chain. Based on a quantitative research conducted at 69 small and medium-sized companies, the paper discusses attitudes of Czech chemical companies towards importance of information and willingness to share it with a key business partner for the purpose of effective management of business operations. While purchase managers marked information concerning extraordinary fluctuations in deliveries and order status information as most important, sales managers saw the highest significance in information about future customer demand and market development. The highest rate of willingness to share information was identified just in the information that was considered by the business partners as most important. For this reason, it is not possible to consider a lack of willingness as a barrier to effective communication among small and medium-sized companies in chemical industry supply chains.
Postoje malých a středních chemických podniků ke sdílení informací v dodavatelských řetězcích
Keywords: information sharing; small and medium-sized enterprises; chemical industry; supply chain; sdílení informací; malé a střední podniky; chemický průmysl; dodavatelský řetězec